Evidence supports the efficacy of Clovis points for hunting proboscideans. (October 2022) - Kilby, J. David; Surovell, Todd A.; Huckell, Bruce B.; Ringstaff, Christopher W.; Hamilton, Marcus J.; Haynes, C. Vance
Highlights: Arguments against the use of Clovis points for hunting proboscideans presented by Eren et al. (2021) are unconvincing. Ethnographic observations show small groups of hunters using spears are capable of bringing down proboscideans. Experimental use of Clovis points on elephant carcasses consistently indicates their effectiveness for imposing potentially lethal wounds. Patterns of complete and broken Clovis points across archaeological site types support their use as hunting weapons. Impact-related damage to Clovis points is consistently present at sites interpreted as proboscidean kills. The preponderance of evidence supports that Clovis points were designed for use in hunting large animals, including proboscideans. Abstract: Clovis projectile points are found in association with mammoths and other proboscideans at multiple sites from across much of North America. The conventional, and arguably parsimonious, explanation for this association is that Clovis points were weapons used to hunt the animals with which they were found. Recently, Eren et al. (2021) argued that experimental data coupled with estimations of mammoth anatomy indicate that Clovis points would not have been effective for proboscidean hunting and were more likely used as cutting tools for scavenging carcasses. We find a number of weaknesses in their argument, including their estimations of mammoth anatomy, the validity of their experimental design, and their assumptions regarding Clovis hunting behavior. We evaluate their argument in light of ethnographic, experimental, and archaeological data and conclude that each of these datasets strongly supports the interpretation of Clovis points as weapons designed for use in hunting large animals, including proboscideans.